2015
DOI: 10.14746/ssllt.2015.5.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Successful language learning in a corporate setting: The role of attribution theory and its relation to intrinsic and extrinsic motivation

Abstract: Attribution theory (Weiner, 1985) and self-determination theory (Deci & Ryan, 1985) have been explored as contributors to L2 motivation (cf. Dörnyei, 2001) but have never been studied quantitatively in concert. In addition, students' attributions for success in learning a foreign language have never been measured through the use of a questionnaire. The aim of this paper is therefore (a) to develop a questionnaire with reliable constructs that allows to measure adult learners' attributions for their success i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
2
5
0
1
Order By: Relevance
“…Based on this notion, the result that the learners in this study reported their L2 improvement indicates that they most likely thought their ability can be enhanced even by a short period of time of practice, leading them to feel more motivated to improve their L2 skills. This finding also lends support to the result of a study on adult learners' attributions by Kálmán and Eugenio (2015), which found that ability significantly contributed to motivation.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Based on this notion, the result that the learners in this study reported their L2 improvement indicates that they most likely thought their ability can be enhanced even by a short period of time of practice, leading them to feel more motivated to improve their L2 skills. This finding also lends support to the result of a study on adult learners' attributions by Kálmán and Eugenio (2015), which found that ability significantly contributed to motivation.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, the learners in the current study referred to the teacher's effective L2 instruction and praise as the reasons for their improved learning attitudes and motivation. At the same time, these attributions uniquely reflect characteristics of the learners in this study, as demonstrated by other studies (e.g., Kálmán & Eugenio, 2015;Mori et al, 2010). The two factors, increased L2 exposure and realization of L2 needs and importance, appear to have had an impact because of the context in which the learners were embedded.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Their results suggest that culture may have an impact on the attributions students give for success and failure. Similarly, Kálmán and Gutierrez (2015) found that another external factor, corporate culture, was the best predictor of success in a study measuring adult L2 learners' attributions in a corporate environment.…”
Section: Attribution Theory and Foreign Language Learning Experiencementioning
confidence: 89%